Arthroscopic Superior Capsular Reconstruction with Dermal Allograft for the Treatment of a Massive Irreparable Rotator Cuff Tear. Issue 3 (July 2020) - Chahla, Jorge; Cancienne, Jourdan M.; Beletsky, Alexander; Manderle, Brandon J.; Verma, Nikhil N.
Abstract : A massive, irreparable rotator cuff tear represents a challenging treatment scenario with respect to surgical intervention. Traditionally, surgical options have included reverse total shoulder arthroplasty, hemiarthroplasty, or rotator cuff repair; however, these techniques may not necessarily restore proper anatomy to the superior capsule, a structure implicated in the maintenance of subacromial contact pressures and the prevention of superior glenohumeral translation. Indications for arthroscopic superior capsular reconstruction include massive, irreparable supraspinatus and/or infraspinatus tears and failure of conservative treatment beyond subjective pain thresholds and dysfunction tolerability. Adequate latissimus dorsi, pectoralis major, and deltoid function helps to ensure the appropriate level of shoulder stability and the ability to complete the necessary rehabilitation protocol. The current surgical guide details the clinical evaluation, surgical technique, and rehabilitation protocol for patients undergoing arthroscopic superior capsular reconstruction for a massive, irreparable rotator cuff tear involving the subscapularis, supraspinatus, and infraspinatus. The procedure is performed arthroscopically with the patient in a beach-chair position, starting first with anterior and lateral portal placement for comprehensive diagnostic shoulder arthroscopy assessing rotator cuff damage. Single-row suture repair of the subscapularis and infraspinatus is performed, followed by concomitant subacromial bursectomy, decompression, and coracoplasty to aid in visualization, avoid graft abrasion, and provide access to marrow elements. Suture anchor placement, allograft fixation, and appropriate suture management are highlighted, as well as rehabilitation timelines, complications, and clinical pearls.